2016
DOI: 10.5210/fm.v21i6.6791
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and enforcing "authentic" identity online: Facebook, real names, and non-normative identities

Abstract: Despite the participatory and democratic promises of Web 2.0, many marginalized individuals with fluid or non-normative identities continue to struggle to represent themselves online. Facebook users, in particular, are told to use “authentic identities,” an idea reinforced throughout the site’s documentation, “real name” and other policies, and in public statements by company representatives. Facebook’s conception of authenticity and real names, however, has created problems for certain users, as demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 0 publications
0
90
0
Order By: Relevance
“…Take real‐name policies. Adopted by SNS like Facebook, these policies suppress names that are not “real enough.” Those affected by these policies include transgender individuals who may not use their birth names (Haimson & Hoffman, ), as well as drag performers (Lingel & Golub, ). Technical features like automated flagging or reporting can amplify authenticity narratives by signaling what types of accounts should be removed—predominately those held by marginalized users (Crawford & Gillespie, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Take real‐name policies. Adopted by SNS like Facebook, these policies suppress names that are not “real enough.” Those affected by these policies include transgender individuals who may not use their birth names (Haimson & Hoffman, ), as well as drag performers (Lingel & Golub, ). Technical features like automated flagging or reporting can amplify authenticity narratives by signaling what types of accounts should be removed—predominately those held by marginalized users (Crawford & Gillespie, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has been accomplished primarily through binary gender classification schemes (Male/Female) [9] and enforcement of "one person per account" policies (e.g., on Facebook). On social media sites like Facebook that forbid pseudonymity and multiple accounts [42], gender transition is often difficult [40]. Presenting oneself online using a post-transition gender, name, and appearance often requires mass trans identity disclosure [40].…”
Section: Trans Identities and Experiences Onlinementioning
confidence: 99%
“…One example is Facebook's real names policy which created difficulties especially for trans people, abuse survivors, and Native Americans. This was widely contested and eventually lead to platform design changes which might be considered a form of delayed and indirect control through user feedback [23]. In a study of ride allocation algorithms on Uber and Lyft, Lee [36] found similar approaches of strategic control by drivers used to cope with overly simplistic mechanisms for driver-rider matching.…”
Section: :12mentioning
confidence: 99%